The Biodiversity of Marine Gastropods of Thailand in the Late Decade. - Sanpanich, Kitithorn; Duangdee, Teerapong (Malaysian Journal of Science, 2013)
This study is mainly based on the collection of marine gastropods along the east coast of the Gulf of Thailand which had been carried out along the coastline in 55 sites from the province of Chonburi to Trad during April 2005 – December 2009. As many habitats as possible were examined at each sites from sandy beaches, muddy sand, rocky shore, and coral reefs. A total of 306 species of gastropods were collected and had been classifi ed in53families 116genera.The most widespread species were Planaxis sulcatus (Planaxidae) and Polinices mammilla (Naticidae) found in 37 sites, followed by Echinolittorina malaccana (Littorinidae) in 35 sites. The highest diversity was 187 species in Trat whereas Koh Mark had the most abundance in this area. The lowest diversity was in Chanthaburi, 88 species, whereas Koh Nomsoa was the most abundant site.The diversity of gastropods in Chonburi was 152 species, whereas Koh Samaesarn and Koh Juang were the most abundant site. 137 species had been found in Rayong and Koh Munnai was the most abundant site. The data from this study had been compared with the resent studies in the late decade from the west coast of the Gulf of Thailand and Andaman Sea.The total gastropods in the late decade were 454 species 205 genera 69 families. (Keywords: marine gastropods, distribution, diversity, Gulf of Thailand)